Serum Responses of Children With Kawasaki Disease Against Severe Acute Respiratory Syndrome Coronavirus 2 Proteins. Issue 11 (November 2020) - Chang, Arthur J.; Croix, Michael; Kenney, Patrick; Baron, Sarah; Hicar, Mark D.
Abstract : With recent reports showing clinical and laboratory overlap of multisystem inflammatory syndrome in children and Kawasaki disease (KD), we addressed the hypothesis that cross coronavirus humoral immunity leads to a parallel postinfectious phenomenon explaining similar pathologic findings in KD and multisystem inflammatory syndrome in children. We demonstrated no cross-reactivity in children with KD but observed some nonspecific interactions postintravenous immunoglobulin infusion.